Leading and sustaining Zimbabwe's private schools: Matching vision with economic reality. (July 2019) - Bush, Tony; Chingarande, Dominica; Glover, Derek; Muchabaiwa, Wonder; Simango, Jubadheya; Thondhlana, Juliet
The political, economic and social challenges in Zimbabwe are well documented. Public schools have been damaged by a shortage of resources, and by a brain drain of teachers. This has led many parents to seek private education for their children but the country's economic problems mean that they often cannot afford to pay the fees. This demanding context informed the authors' study of leadership in 12 private schools in Harare and the surrounding area. Individual and focus group interviews were conducted with 19 leaders in these schools. The findings show that most of the schools have experienced significant falls in student numbers, despite cutting fees. This creates a severe management challenge for principals, other leaders and school owners. There have been redundancies at several of the schools, which the leaders find stressful, while salary levels remain modest although still higher than those in the public sector. The infrastructure and facilities are generally good compared to those in the public sector but leaders lament that they cannot be enhanced in the current financial climate. Most of the schools have a distinctive Christian ethos, and a vision to provide the best possible education for their children, but the leaders' ambitious plans are thwarted by Zimbabwe's harsh economic realities.